Preparation method of nano zinc oxide core antibacterial and detoxicating auxiliary agent

By preparing nano zinc oxide nuclear antibacterial and detoxicating additives, the core-shell structure of modified nano zinc oxide and the film-forming properties of silk fibroin have been solved, and the problem of poor antibacterial and antiviral effects in the prior art has been achieved, thus achieving high efficiency Bacterial and virus killing and long-term antibacterial effects.

CN119318347APending Publication Date: 2025-01-17CHINA KRYPTON NEW ENERGY TECH (SHANGHAI) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411491546.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The prior art is difficult to effectively antibacterial and antiviral, especially in the face of bacteria and fungi that are common in the living environment, and lacks efficient antibacterial and antiviral additives.

Method used

By preparing nano zinc oxide nuclear antibacterial detoxication additives, zinc acetate, polyethylene glycol, sodium hydroxide and other materials are used, and treated by ball milling, ultrasonic dispersion, butyl titanate hydrolysis, silk fibroin and somatosin, to form Modified nano zinc oxide to form a core-shell structure with titanium dioxide as the shell and nano zinc oxide as the core, enhancing antibacterial and antiviral properties.

Benefits of technology

It significantly improves the antibacterial and antitoxic effect, can kill bacteria and viruses, enhances the stability and durability of additives, and ensures long-term antibacterial effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a preparation method of a nano-zinc oxide core antibacterial and detoxification auxiliary agent, and belongs to the technical field of antibacterial and antiviral inorganic materials. According to the preparation method disclosed by the invention, the antibacterial and detoxicating auxiliary agent taking nano zinc oxide as a core is prepared, a modified nano zinc oxide solid with a shell being titanium dioxide is obtained through hydrolysis and roasting of butyl titanate, and the surface of the solid is modified through silk fibroin, so that the overall antibacterial and detoxicating effect of the auxiliary agent is improved, and the effect of killing bacteria and viruses is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antibacterial and antiviral inorganic materials, and relates to a method for preparing a nano zinc oxide core antibacterial and detoxifying auxiliary agent. Background Art

[0002] Nano zinc oxide, as a new type of multifunctional inorganic nanomaterial, has excellent antibacterial properties and combines the advantages of nanocrystals. Its antibacterial properties are better than those of ordinary nano zinc oxide and has become one of the hot topics in the research of inorganic antibacterial agents.

[0003] Nowadays, various bacteria and fungi are commonly found in the living environment. Therefore, there is an urgent need for an effective antibacterial and antiviral auxiliary agent in the prior art. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a nano zinc oxide core antibacterial and detoxifying auxiliary agent, and the prepared auxiliary agent has excellent antibacterial and antiviral properties.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a nano zinc oxide core antibacterial and detoxifying auxiliary agent comprises the following preparation steps: S1. Evenly mix a 0.1-0.2 mol / L zinc acetate aqueous solution and polyethylene glycol 200 to obtain a mixed solution; heat to 85-90°C, add sodium hydroxide solution, and stir for 2-3 h, wherein the volume ratio of zinc acetate aqueous solution, polyethylene glycol 200 and sodium hydroxide solution is 5:(1-1.5):5; after stirring, cool to room temperature, filter, wash with deionized water, dry at 55-60°C for 5 h, and then calcine to obtain nano zinc oxide solid; S2, grinding the nano zinc oxide solid by ball mill at a speed of 400 r / min for 3-5 h, and passing through a 200 mesh sieve to obtain nano zinc oxide powder; S3, mixing nano zinc oxide powder with a solid-liquid ratio of 1: (20-30) with deionized water, and performing ultrasonic dispersion for 10-20 minutes to obtain a nano zinc oxide dispersion; By weight, acetic acid is added to 30 to 50 parts of a nano zinc oxide dispersion to make the pH value of the nano zinc oxide dispersion 1.7, and then 15 to 20 parts of butyl titanate are added, and the mixture is stirred at a speed of 400 r / min at room temperature for 8 to 12 hours to obtain a mixed solution, the mixed solution is centrifuged, the solid is collected and washed with anhydrous ethanol and deionized water in sequence, dried in a vacuum drying oven, and finally calcined to obtain modified nano zinc oxide; S4. After calcium chloride, ethanol and deionized water are evenly mixed to obtain a calcium chloride mixed solution, add silk fibroin and pine fibroin, heat to 40-45°C, stir at a speed of 200-300 r / min for 15-20 min, continue to add modified nano zinc oxide, increase the speed to 600-800 r / min, and continue stirring for 2-4 h; after stirring, perform high-speed centrifugation for 20-25 min, filter, take out the solid, wash it with anhydrous ethanol and deionized water in turn, vacuum dry it, and then grind it with a ball mill at a speed of 400 r / min for 3-5 h, and pass it through a 200-mesh sieve to prepare the nano zinc oxide core antibacterial and detoxification auxiliary agent.

[0006] As a preferred technical solution of the present invention, in step S1, the concentration of the sodium hydroxide solution is 0.1-0.2 mol / L.

[0007] As a preferred technical solution of the present invention, in step S1, the calcination temperature is 450-500°C and the calcination time is 5-7h.

[0008] As a preferred technical solution of the present invention, in step S1, the rotation speed during stirring is 500-600 r / min.

[0009] As a preferred technical solution of the present invention, in step S3, the calcination temperature is 500-600°C and the calcination time is 2-4 hours.

[0010] As a preferred technical solution of the present invention, in step S3, the drying temperature is 60-80°C and the drying time is 10-13 hours.

[0011] As a preferred technical solution of the present invention, in step S4, the mass ratio of calcium chloride, ethanol and deionized water in the calcium chloride mixed solution is (0.7~1):3:10.

[0012] As a preferred technical solution of the present invention, in step S4, the vacuum drying temperature is 70-90° C. and the time is 10-13 h.

[0013] As a preferred technical solution of the present invention, in step S4, the amount of the calcium chloride mixed solution added is 13-20 parts, the amount of silk fibroin added is 4-7 parts, and the amount of pine suline added is 1-2 parts by weight.

[0014] As a preferred technical solution of the present invention, in step S4, the amount of the modified nano zinc oxide added is 10 to 16 parts by weight.

[0015] The invention adds polyethylene glycol when preparing nano zinc oxide, and utilizes the steric hindrance effect to reduce the surface tension of the particles and the bonding between the particles, thereby effectively reducing the particle size of the nano zinc oxide; at the same time, the polyethylene glycol, as a surfactant, can be wrapped on the surface of the nano zinc oxide particles to prevent the particles from colliding with each other and agglomerating, thereby improving the dispersibility of the nano zinc oxide.

[0016] The nano zinc oxide dispersion is mixed with butyl titanate, and the modified nano zinc oxide is obtained by hydrolyzing and calcining the butyl titanate. The modified nano zinc oxide is a core-shell structure with titanium dioxide as the shell and nano zinc oxide as the core. Titanium dioxide is an excellent antibacterial and antiviral material that can produce superoxide radicals and hydroxyl radicals under light irradiation. These free radicals have strong oxidizing properties and can cause the decomposition of bacterial proteins and lipids, thereby killing bacteria.

[0017] Silk fibroin is a natural protein polymer macromolecule, which has the characteristics of flexible molecular chain, good biocompatibility and easy film formation. In the present invention, the film-forming property is utilized, and the silk fibroin is dissolved in a ternary solvent of calcium chloride, ethanol and deionized water, and can be coated on the surface of the modified nano zinc oxide solid by standing and drying under vacuum conditions. After the modification by the silk fibroin, on the one hand, the cytotoxicity of the modified nano zinc oxide itself can be significantly reduced, and at the same time, the silk fibroin can enhance the interaction between the modified nano zinc oxide and the organism through its unique molecular structure and biocompatibility, and improve its antibacterial effect through the synergistic effect of the antibacterial mechanism of the modified nano zinc oxide itself (such as photocatalysis, zinc ion dissolution, generation of active oxygen, etc.) and the biocompatibility and stability of the silk fibroin. And because the coating of the silk fibroin can protect the modified nano zinc oxide from the influence of the external environment, prevent it from aggregation and inactivation, thereby enhancing its stability and durability.

[0018] At the same time, pine spores are added while modifying the modified nano zinc oxide with silk fibroin. The pine spores have good antibacterial and antioxidant properties and can inhibit the growth of a variety of bacteria. The pine spores are loaded on the surface of the modified nano zinc oxide through the film-forming effect of silk fibroin. Due to the addition of pine spores, the overall antibacterial performance is further improved. At the same time, the carrier effect of the modified nano zinc oxide helps to protect the pine spore molecules and prevent them from being destroyed or degraded by the external environment, thereby improving the stability and durability of the pine spores, which is conducive to maintaining a long-term antibacterial effect in practical applications.

[0019] Beneficial effects of the present invention: The present invention prepares an antibacterial and detoxifying auxiliary agent with nano zinc oxide as the core, obtains modified nano zinc oxide with a titanium dioxide shell by hydrolyzing and calcining butyl titanate, and modifies the solid surface by silk fibroin, thereby improving the overall antibacterial and detoxifying effect of the auxiliary agent and achieving the effect of killing bacteria and viruses. DETAILED DESCRIPTION

[0020] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0021] In the comparative examples and embodiments of the present invention: Shengsongsu: purchased from Shanghai Myril Biochemical Technology Co., Ltd.; Silk fibroin: purchased from Shanghai Future Industrial Co., Ltd. Zinc acetate: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: Z820737; Polyethylene glycol 200: purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd.; Calcium chloride: purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd., product number: 1085159; Butyl titanate: purchased from Jinan Jinbang Environmental Protection Technology Co., Ltd.

[0022] Example 1 S1. Evenly mix a 0.15 mol / L zinc acetate aqueous solution and polyethylene glycol 200 to obtain a mixed solution; heat to 88°C, add a 0.15 mol / L sodium hydroxide solution, and stir at a speed of 550 r / min for 2.5 h, wherein the volume ratio of the zinc acetate aqueous solution, polyethylene glycol 200 and the sodium hydroxide solution is 5:1.3:5; after stirring, cool to room temperature, filter, wash with deionized water, dry at 58°C for 5 h, and then calcine at 480°C for 6 h to obtain nano zinc oxide solid; S2, grinding the nano zinc oxide solid by ball mill at a speed of 400 r / min for 4 h, and passing through a 200 mesh sieve to obtain nano zinc oxide powder; S3, mixing nano zinc oxide powder with a solid-liquid ratio of 1:25 with deionized water, and performing ultrasonic dispersion for 15 minutes to obtain a nano zinc oxide dispersion; By weight, acetic acid is added to 40 parts of nano zinc oxide dispersion to make the pH value of the nano zinc oxide dispersion 1.7, and then 18 parts of butyl titanate are added, and the mixture is stirred at a speed of 400 r / min at room temperature for 10 hours to obtain a mixed solution, the mixed solution is centrifuged, the solid is collected and washed with anhydrous ethanol and deionized water in sequence, and then placed in a vacuum drying oven at 70° C. for 12 hours, and finally calcined at 550° C. for 3 hours to obtain modified nano zinc oxide; S4. In parts by weight, 5 parts of silk fibroin and 1.5 parts of pine suline are added to 16 parts of calcium chloride mixed solution obtained by evenly mixing calcium chloride, ethanol and deionized water, the temperature is raised to 43°C, and the mixture is stirred at a speed of 250 r / min for 18 min. 14 parts of modified nano zinc oxide are added, the speed is increased to 700 r / min, and the stirring is continued for 3 h. After the stirring is completed, high-speed centrifugation is performed for 22 min, and then filtered, washed with anhydrous ethanol and deionized water in turn, and then vacuum dried at 80°C for 12 h, and then ground with a ball mill at a speed of 400 r / min for 3 h, and passed through a 200-mesh sieve to prepare the nano zinc oxide core antibacterial and detoxification auxiliary agent, wherein the mass ratio of calcium chloride, ethanol and deionized water in the calcium chloride mixed solution is 0.8:3:10.

[0023] Example 2 S1. Evenly mix a 0.1 mol / L zinc acetate aqueous solution and polyethylene glycol 200 to obtain a mixed solution; heat to 85°C, add a 0.1 mol / L sodium hydroxide solution, and stir at a speed of 500 r / min for 2 hours, wherein the volume ratio of the zinc acetate aqueous solution, polyethylene glycol 200 and the sodium hydroxide solution is 5:1:5; after stirring, cool to room temperature, filter, wash with deionized water, dry at 55°C for 5 hours, and then calcine at 450°C for 5 hours to obtain nano zinc oxide solid; S2, grinding the nano zinc oxide solid by ball mill at a speed of 400 r / min for 3 h, and passing through a 200 mesh sieve to obtain nano zinc oxide powder; S3, mixing nano zinc oxide powder with a solid-liquid ratio of 1:20 with deionized water, and performing ultrasonic dispersion for 10 minutes to obtain a nano zinc oxide dispersion; By weight, acetic acid is added to 30 parts of nano zinc oxide dispersion to make the pH value of the nano zinc oxide dispersion 1.7, and then 15 parts of butyl titanate are added, and the mixture is stirred at a speed of 400 r / min at room temperature for 8 hours to obtain a mixed solution, the mixed solution is centrifuged, the solid is collected and washed with anhydrous ethanol and deionized water in sequence, and then placed in a vacuum drying oven at 60° C. for 10 hours, and finally calcined at 500° C. for 2 hours to obtain modified nano zinc oxide; S4. In parts by weight, 4 parts of silk fibroin and 1 part of pine suline are added to 13 parts of calcium chloride mixed solution obtained by evenly mixing calcium chloride, ethanol and deionized water, the temperature is raised to 40°C, stirred at a speed of 200 r / min for 15 min, 10 parts of modified nano zinc oxide are added, the speed is increased to 600 r / min, and stirring is continued for 2 h; after stirring, high-speed centrifugation is performed for 20 min, and then filtered, washed with anhydrous ethanol and deionized water in turn, and then vacuum dried at 70°C for 10 h, and then ground with a ball mill at a speed of 400 r / min for 4 h, and passed through a 200-mesh sieve to prepare the nano zinc oxide core antibacterial and detoxification auxiliary agent, wherein the mass ratio of calcium chloride, ethanol and deionized water in the calcium chloride mixed solution is 0.7:3:10.

[0024] Example 3 S1. Evenly mix a 0.2 mol / L zinc acetate aqueous solution and polyethylene glycol 200 to obtain a mixed solution; heat to 90°C, add a 0.2 mol / L sodium hydroxide solution, and stir at a speed of 600 r / min for 3 h, wherein the volume ratio of the zinc acetate aqueous solution, polyethylene glycol 200 and the sodium hydroxide solution is 5:1.5:5; after stirring, cool to room temperature, filter, wash with deionized water, dry at 60°C for 5 h, and then calcine at 500°C for 7 h to obtain nano zinc oxide solid; S2, grinding the nano zinc oxide solid by ball mill at a speed of 400 r / min for 5 h, and passing through a 200 mesh sieve to obtain nano zinc oxide powder; S3, mixing nano zinc oxide powder with a solid-liquid ratio of 1:30 with deionized water, and performing ultrasonic dispersion for 20 minutes to obtain a nano zinc oxide dispersion; By weight, acetic acid is added to 50 parts of a nano zinc oxide dispersion to make the pH value of the nano zinc oxide dispersion 1.7, and then 20 parts of butyl titanate are added, and the mixture is stirred at a speed of 400 r / min at room temperature for 12 hours to obtain a mixed solution, the mixed solution is centrifuged, and the solid is collected and washed with anhydrous ethanol and deionized water in sequence, and then placed in a vacuum drying oven at 80° C. for 13 hours, and finally calcined at 600° C. for 4 hours to obtain a modified nano zinc oxide; S4. In parts by weight, 7 parts of silk fibroin and 2 parts of pine suline are added to 20 parts of a calcium chloride mixed solution obtained by uniformly mixing calcium chloride, ethanol and deionized water, the temperature is raised to 45°C, and the mixture is stirred at a speed of 300 r / min for 20 min. 16 parts of modified nano zinc oxide are added, the speed is increased to 800 r / min, and the stirring is continued for 4 h. After the stirring is completed, the mixture is treated by high-speed centrifugation for 25 min, filtered, washed with anhydrous ethanol and deionized water in turn, and then vacuum dried at 90°C for 13 h. The mixture is then ground with a ball mill at a speed of 400 r / min for 5 h, and passed through a 200-mesh sieve to prepare the nano zinc oxide core antibacterial and detoxification auxiliary agent, wherein the mass ratio of calcium chloride, ethanol and deionized water in the calcium chloride mixed solution is 1:3:10.

[0025] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that polyethylene glycol 200 is not added in step S1 of Comparative Example 1, and the other operations are the same.

[0026] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that no pinocybin is added in step S4 of Comparative Example 2, and the other operations are the same.

[0027] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in step S4 of Comparative Example 3, the silk fibroin modification treatment is not performed, and the other operations are the same.

[0028] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that step S4 is not performed in Comparative Example 4, and the remaining operations are the same.

[0029] Performance Testing: 1. Using the colony counting method, Staphylococcus aureus (AATCC6538P; Gram-positive bacteria) and Escherichia coli (AATCC8099; Gram-negative bacteria) were selected as the test bacteria, and the inoculation concentration of Staphylococcus aureus was 9.6×10 6 CFU / mL; E. coli inoculation concentration was 5.1×10 6 CFU / mL, antibacterial rate after 24 h of testing; 2. Test reference According to the "Technical Specifications for Disinfection" (2002 Edition), the antiviral activity was tested. Taking the N1H1 influenza virus as an example, the results are as follows:

[0030] According to the above data, it can be seen that the antibacterial and antiviral properties of the antibacterial and detoxifying auxiliary agent prepared by the present invention are excellent.

[0031] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a nano zinc oxide core antibacterial and detoxifying auxiliary agent, characterized in that: The method comprises the following preparation steps: S1. Evenly mix a 0.1-0.2 mol / L zinc acetate aqueous solution and polyethylene glycol 200 to obtain a mixed solution; heat to 85-90°C, add sodium hydroxide solution, and stir for 2-3 h, wherein the volume ratio of zinc acetate aqueous solution, polyethylene glycol 200 and sodium hydroxide solution is 5:(1-1.5):5; after stirring, cool to room temperature, filter, wash with deionized water, dry at 55-60°C for 5 h, and then calcine to obtain nano zinc oxide solid; S2, grinding the nano zinc oxide solid by ball mill at a speed of 400 r / min for 3-5 h, and passing through a 200 mesh sieve to obtain nano zinc oxide powder; S3, mixing nano zinc oxide powder with a solid-liquid ratio of 1: (20-30) with deionized water, and performing ultrasonic dispersion for 10-20 minutes to obtain a nano zinc oxide dispersion; By weight, acetic acid is added to 30 to 50 parts of a nano zinc oxide dispersion to make the pH value of the nano zinc oxide dispersion 1.7, and then 15 to 20 parts of butyl titanate are added, and the mixture is stirred at a speed of 400 r / min at room temperature for 8 to 12 hours to obtain a mixed solution, the mixed solution is centrifuged, the solid is collected and washed with anhydrous ethanol and deionized water in sequence, dried in a vacuum drying oven, and finally calcined to obtain modified nano zinc oxide; S4. After calcium chloride, ethanol and deionized water are evenly mixed to obtain a calcium chloride mixed solution, add silk fibroin and pine fibroin, heat to 40-45°C, stir at a speed of 200-300 r / min for 15-20 min, continue to add modified nano zinc oxide, increase the speed to 600-800 r / min, and continue stirring for 2-4 h; after stirring, perform high-speed centrifugation for 20-25 min, filter, take out the solid, wash it with anhydrous ethanol and deionized water in turn, vacuum dry it, and then grind it with a ball mill at a speed of 400 r / min for 3-5 h, and pass it through a 200-mesh sieve to prepare the nano zinc oxide core antibacterial and detoxification auxiliary agent.

2. The method for preparing the nano zinc oxide core antibacterial and detoxifying auxiliary agent according to claim 1, characterized in that: In step S1, the concentration of the sodium hydroxide solution is 0.1-0.2 mol / L.

3. The method for preparing the nano zinc oxide core antibacterial and detoxifying auxiliary agent according to claim 1, characterized in that: In step S1, the calcination temperature is 450-500°C and the calcination time is 5-7 hours.

4. The method for preparing the nano zinc oxide core antibacterial and detoxifying auxiliary agent according to claim 1, characterized in that: In step S1, the rotation speed during stirring is 500-600 r / min.

5. The method for preparing the nano zinc oxide core antibacterial and detoxifying auxiliary agent according to claim 1, characterized in that: In step S3, the calcination temperature is 500-600° C. and the calcination time is 2-4 hours.

6. The method for preparing the nano zinc oxide core antibacterial and detoxifying auxiliary agent according to claim 1, characterized in that: In step S3, the drying temperature is 60-80° C. and the drying time is 10-13 hours.

7. The method for preparing the nano zinc oxide core antibacterial and detoxifying auxiliary agent according to claim 1, characterized in that: In step S4, the mass ratio of calcium chloride, ethanol and deionized water in the calcium chloride mixed solution is (0.7~1):3:

10.

8. The method for preparing the nano zinc oxide core antibacterial and detoxifying auxiliary agent according to claim 1, characterized in that: In step S4, the vacuum drying is carried out at a temperature of 70-90° C. and for a time of 10-13 hours.

9. The method for preparing the nano zinc oxide core antibacterial and detoxifying auxiliary agent according to claim 1, characterized in that: In step S4, in parts by weight, the amount of the calcium chloride mixed solution added is 13-20 parts, the amount of silk fibroin added is 4-7 parts, and the amount of pine suline added is 1-2 parts.

10. The method for preparing the nano zinc oxide core antibacterial and detoxifying auxiliary agent according to claim 1, characterized in that: In step S4, the amount of modified nano zinc oxide added is 10 to 16 parts by weight.

Citation Information

Cited By

  • Antibacterial and detoxicating leather finishing agent and preparation method thereof

    CN121136584A